Is pinworm infection still a public health concern among children in resource-rich regions? Trends in pinworm infection prevalence and associated factors among children in Hualien County, Taiwan: a retrospective cross-sectional study - Yu-Chao Hsiao; Jen-Hung Wang; Chia-Hsiang Chu; Yu-Hsun Chang; Yung-Chieh Chang; Rong-Hwa Jan; Shao-Yin Chu; Shang-Hsien Yang; Jui-Shia Chen; Ming-Chun Chen (BMC, 2022)
Abstract Background Enterobius vermicularis (pinworm) is a common intestinal parasitic infection in children. A gradual decrease in the prevalence of pinworm infection has been noted in resource-rich settings, such as Taiwan. However, the influence of sociodemographic factors on the temporal trend in pinworm infection rates in children under the current pinworm infection prevention policy in Taiwan is not well characterized. This study aimed to evaluate the trend of pinworm infection prevalence and the associated factors among children in Hualien County, Taiwan. Methodology In this retrospective cross-sectional study, we included a total of 56,197 students (aged 6-10 years) in grades 1 and 4 in Hualien in 2009-2018. Children were screened for pinworm infection using adhesive cellophane perianal swabs in the routine student health examination. Logistic regression was conducted to evaluate the factors associated with pinworm infection. Associations between dependent and independent variables were measured by odds ratios. The Cochran-Armitage test was used to assess whether there were significant trends in different stratifications. Variables with P-values < 0.05 were considered statistically significant. Results A total of 56,197 school-age children from grades 1 and 4 during 2009-2018 were included. Young age and male sex were risk factors for pinworm infection (P < 0.001). A negative correlation between body mass index and enterobiasis was observed, and decreased pinworm infection was noted during the study reference period. Children living in suburban and rural areas had higher odds of having a pinworm infection than those living in urban areas (P < 0.001). A significant decrease in the overall prevalence rate of pinworm infection was observed among children in 2009-2018 (P < 0.001). However, there was no obvious change in the pinworm infection rate in rural areas during this period (P = 0.953), and it was higher than that in urban and suburban areas. Conclusions The overall prevalence of pinworm infection gradually decreased from 2009 to 2018 among school-age children in Hualien. However, there was no declining trend in pinworm infection in rural areas. Young age, male sex, and rural residence were significantly associated with pinworm infection. Pinworm infection remains a major public health concern among children in rural areas of Hualien.